A questão da legitimação para a tutela dos interesses coletivos: uma perspectiva do pensamento de Mauro Cappelletti - Costa, Paulo Rogério Bastos (2013)
This present work broaches the question of legitimation when proposing protection in advocacy of collective interests, under the thinking of Mauro Cappelletti, which emphasizes the sense of intermediary bodies. On the first chapter, it approaches the evolution of collective interest s conception and the bodies that could invocate its protection. On the second chapter, discusses the appearance of the Brazilian Legal System protection of collective interests, following and its orientation that emphasizes the State as an agent to claim protection to collective interests mainly by Public Prosecutor s Office. The third chapter concentrates on analyzing the article Formazioni sociale e interesse di grupo davanti ala giustizia civile from Mauro Cappelletti (1975), where the subject is discussed. Finally, the fourth chapter exposes the legitimation for the defense of collective interests by intermediary bodies, understood as contemporary third-sector Nongovernmental Organizations (NGOs), and indicated as more viable solutions to the question of the effectiveness on the defense of collective interests, as well the modern political thinking of Minimal State. As conclusion, it is defended that NGOs should be increasingly involved with the challenge of acting on protection of the collective interests